Long-term continuity and change within Hebridean and mainland Scottish island dwellings - Lenfert, R. (2012)
Small island dwellings in Scotland and Ireland, typically (and often problematically) referred to as crannogs, have experienced growing archaeological activity in the past three decades through survey, underwater investigation and excavation. This renewed activity has prompted a number of recent research projects, both field and desk based in nature. While the end result has certainly created a clearer picture of life on small islets from the Neolithic to the Post-Medieval period, particularly in Scotland there are several fundamental aspects that are long overdue for attention. First, rather than focussing upon niche periods such as the Iron Age, I have chosen to examine continuity and change over the entirety of the island dwelling tradition in Scotland. Secondly, this thesis also marks a departure from traditional approaches by integrating mainland crannog studies with those found in the Western Isles or Outer Hebrides. Despite having the highest density and longest chronology for occupied islets in Scotland, very little fieldwork has been carried out in the Western Isles. Ironically, examples in the Western Isles, generally referred to as 'island duns', have typically been viewed in isolation from their mainland counterpart the 'crannog', despite Hebridean activity appearing to embrace the concept more fully. Ultimately, it is the recognition in this thesis that both areas share the same core concept- living on small islets, and how the integration of Hebridean sites into existing discourses on mainland occupied islets can be mutually beneficial. This thesis wishes to reddress this imbalance while also examining how archaeological terminology can divide the common conceptual denominator of living on small islets. Another aspect includes an examination of the phenomena of prolific reuse amongst island dwellings, as almost every islet excavation in Scotland has provided evidence of reuse, often several centuries or more after initial occupation. Therefore, another aim of this thesis is to analyse use patterns over the long-term, and examine why people repeatedly went to the effort of living on small islets. This thesis also indicates how the motivations for islet use range from pragmatic to more symbolic concerns. These underlying motivations for islet use in Scotland are found to vary greatly, and extend beyond the typical defence hypothesis.